Guía didáctica a través de material no estructurado sobre geografía física del Ecuador para el aprendizaje de los estudiantes con discapacidad visual del centro de apoyo educativo especializado APRODVICH – Riobamba - Ocaña Castillo, Galo Arsube (2021)
The research work "DIDACTIC GUIDE THROUGH NON-STRUCTURED MATERIAL ON PHYSICAL GEOGRAPHY OF ECUADOR FOR THE LEARNING OF STUDENTS WITH VISUAL IMPAIRMENTS AT APRODVICH SPECIALIZED EDUCATIONAL SUPPORT CENTER - RIOBAMBA." It aims to improve students with visual impairment and the quality of teaching for APRODVICH instructors in the field of Physical Geography of Ecuador. It can be through the use of the material in high relief and Braille writing. It uses information gathering techniques such as the survey and the interview. It was determined that managers, teachers, and students require a didactic guide with materials, didactic resources, and methodological practices in high relief and Braille writing on topics related to Physical Geography. This didactic guide is necessary for the development and understanding of their educational activities. Since they only use basic modules, materials, and traditional methodology. A didactic guide is a helpful tool to guide students, to strengthen their knowledge about the Physical Geography of Ecuador complemented with the political, ecological, and road map. Thus, it is possible for blind students to identify each map using their hands. It guarantees inclusion and equal educational opportunities. For this reason, it is recommended that authorities from the support center apply the didactic guide using unstructured materials in high relief and Braille writing to maximize and enhance the intellectual skills of students with visual impairments